Mechanical design of a robot type agv "automated guided vehicle" (2008)
The development of automatic robots is one of the felds of research of fexible manufacturing systems (FMS), where the main goal is to carry out tasks in the area of logistics, reducing human intervention, searching automate repetitive tasks or inappropriate for the workers. This article presents the design of an AGV, Automated Guided Vehicle, as part of a FMS and proposes a mechatronics design methodology supported in tools CAD and CAE, in the areas of mechanics, electronics and control, giving rise to the construction of the prototype.